Selection and induction of supervisors for fieldwork: experiences from Young Lives in Peru - Penny, M; Oré, B; Madrid, S (Young Lives, 2012)
The household and child survey that lies at the heart of Young Lives study is carried out every three years by a dedicated team of fieldworkers working alongside each country’s lead researcher. The field teams are responsible for locating the families, maintaining their interest and willingness to participate over the entire 15 years of the study, and collecting the large amount of information that is the basis of the research. The Young Lives children in Peru live in communities that are spread across the country and the survey teams have to be able to function as independent units, travelling for considerable periods of time, sometimes in difficult conditions. Having teams that are capable of facing these challenges, and are well prepared for them, is critical to data quality and the success of the study. This Technical Note gives an overview of the recruitment and training processes we followed to try to ensure that teams were cohesive, mutually supportive, and well prepared for the work in Peru. We describe the process with the intention of sharing our experience and stimulating discussion, innovation and research in this area.